PENERAPAN STRATEGI PEMASARAN STP PADA PT. GUESTPRO - Komang Setiawan; Kadek Wulandari Laksmi P; I G. N. Oka Ariwangsa; Ni Wayan Lasmi (Universitas Majalengka, 2022)
GuestPro is an information technology company based in Ubud – Bali, which provides information system solutions for tourism & hospitality industry companies that want to survive in the midst of intense business competition in this industry. As time goes by, technology is very important to sustain any changes in the times that continue to develop. The company will be great if it is able to attract customers to a product. Where in the current situation, namely the COVID-19 pandemic, companies are required to take advantage of everything to survive by reducing operational costs to reduce expenses. Various strategies can be applied by the company in accordance with the conditions and capabilities of the company. Therefore the marketing process in a company will be very important if it is combined with the right technology. STP marketing strategy is one way to market a company's products easily and efficiently. The company will start to record every income and expenditure in order to get a balanced result to reduce losses.